2020
DOI: 10.24843/lkjiti.2020.v11.i02.p02
|View full text |Cite
|
Sign up to set email alerts
|

End User Satisfaction for Location Health Service Application with Analysis of Task Technology Fit

Abstract: There are several types of health services that provide information about health care facilities, such as pharmacies, health centers, clinics, and hospitals. Application of health service facilities location is used to facilitate users in reaching the nearest health service facility. The application of the health care facilities location has not been optimally used by the user so often. The advantage of analyzing the system is to determine its direct and indirect effect on the end-user. This research analyzes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
3
0
3
Order By: Relevance
“…TTF seeks to assess whether the technology's functionality is well aligned, i.e., compatible with the work done by end users. Studies have shown that technology will be more readily accepted and have a positive impact on individual performance if the technological characteristics match expected tasks [119][120][121][122][123][124][125][126].…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…TTF seeks to assess whether the technology's functionality is well aligned, i.e., compatible with the work done by end users. Studies have shown that technology will be more readily accepted and have a positive impact on individual performance if the technological characteristics match expected tasks [119][120][121][122][123][124][125][126].…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…The user of an IT seeks to improve their performance by improving the way they work, perform their tasks and achieve their objectives [122,137,138]. Other studies in the field of health have focused on the application of the TTF model based on end-user satisfaction [126,139].…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Aparatur Sipil Negara (ASN) perlu mewujudkan birokrasi yang efektif dan efisien di instansi pemerintah sehingga terwujudnya good governance. Dengan berkembanganya birokrasi yang ada di Indonesia serta pertumbuhan tuntutan pelayanan penyelenggara negara yang cepat dan tepat maka ASN harus memiliki inovasi demi tercapainya tujuan bernegara [4]. Kemajuan teknologi informasi dan komunikasi telah menjadi sarana yang penting dalam mewujudkan pelayanan publik yang berbasis pada good governance.…”
Section: Pendahuluanunclassified
“…Tahapan identifikasi masalah merupakan tahapan untuk memperispakan kemungkinankemungkinan yang sekiranya terdapat dalam sebuah usaha bisnis Jaginow Bali khususnya dalam areal Supply Chain Management (SCM), serta mempersiapkan tools Enterprise Resource Planning (ERP) yang akan dijadikan tools dalam penelitian yang dilakukan. Penggunaan aplikasi yang tepat merupakan suatu tindakan untuk mempelajari karakteristik dan menambah pengetahuan terkait penggunaan sistem untuk mengukur kesiapan dan kepuasan pengguna akhir [8].…”
Section: Identifikasi Masalahunclassified